Literature Reviews: Role Situational Leadership in Improving Teacher Performance - Tuerah, Philotheus E A; Sumual, Shelty D.M.; Lumapow, Harol R.; Dondokambey, Rainier N; Dotulung, Reza A. W.; Paath, Deicy (International Journal of Information Technology and Education, 2024)
Teacher performance plays a role in increasing student motivation and learning outcomes. This research aims to provide an overview of the relationship between situational leadership and performance. The research method used is qualitative with a literature review. Search for articles using Google Scholar with the keywords "situational leadership" and "employee performance". The articles selected were from 2016 to 2023. A total of 30 research articles were selected and then an overview was provided. The research results found that 11 out of 30 articles stated an insignificant relationship between situational leadership and performance and sustainability stated a significant relationship. Only 1 out of 30 articles researched had an educational nuance. Most research articles come from Indonesia. Future research can use mediation to link situational leadership with teacher performance such as job satisfaction, work motivation, employee sustainability, organizational citizenship behavior, and total quality management.